Spectrum of Upper Limb Surgeries Performed Under Supraclavicular Brachial Plexus Block in a Tertiary Care Hospital: A One-year Review (Eastern Medical College Journal, 2026)
Background: The supraclavicular brachial plexus block (SCB) is a widely used regional anesthesia technique for upper limb surgeries. It offers excellent surgical anesthesia and postoperative analgesia, with minimal systemic effects. This study aimed to analyze the types and frequency of upper limb surgeries conducted under SCB over one year in a tertiary care hospital, assessing its clinical applicability and success rates.Materials & Methods: A prospective observational study was conducted in Eastern Medical College Hospital from January 2024 to December 2024. A total of 100 patients underwent upper limb surgeries under supraclavicular block was included in this study which were selected by purposive sampling. patient demographics, type of surgery, side and level of surgery, block success rate, intraoperative complications and postoperative analgesia duration and complications were recorded in data collection sheet. Data was entered into Microsoft Excel and analyzed using SPSS version 25.0. Categorical variables were expressed as frequencies and percentages.Results: Among the 100 participants mostly were male (65%) compared to female cases (35%). Surgeries on the right upper limb (80%) were more common than those on the left upper limb (20%). The block had a high success rate of 98% with no intraoperative complications. Conversion to general anesthesia was required in 2% of cases. The wrist was the most common surgical site (61%), followed by the hand (18%), elbow (11%) and forearm (10%). Most surgeries were for combined fractures of the radius and ulna (50 cases), followed by isolated radius fractures (20 cases), while ulna fractures, hand fractures, tendon repairs, soft tissue repairs, and implant removals each accounted for 5 to 10 cases.Conclusion: The supraclavicular block is a reliable and effective regional anesthesia technique for a wide range of upper limb surgeries in a tertiary care setting. Its use is associated with high success rates, minimal complications, and satisfactory postoperative analgesia, making it a valuable anesthetic option for upper extremity surgical procedures.Eastern Med Coll J. July 2025; 10 (2): 127-131